Signaling with private monitoring - Gonzalo Cisternas; Aaron Kolb (Federal Reserve Bank of New York, 2021)
We study dynamic signaling when the informed party does not observe the signals generated by her actions. A forward-looking sender signals her type continuously over time to a myopic receiver who privately monitors her behavior; in turn, the receiver transmits his private inferences back through an imperfect public signal of his actions. Preferences are linear-quadratic and the information structure is Gaussian. We construct linear Markov equilibria using belief states up to the sender's second-order belief. Because of the private monitoring, this state is an explicit function of the sender's past play, leading to a novel separation effect through the second-order belief channel. Applications to models of organizations and reputation are examined.
Keywords: C73; D82; D83; 330; signaling; private monitoring; continuous time